Lifelong Learning Pathways : Addressing Participation and Diversity in Higher Education : Final Report. - McLaughlin, Patricia; Mills, Anthony; Davis, Peter; Saha, Swapan; Smith, Peter; Hardie, Mary (Office for Learning and Teaching, 2013)
Final report from a project that examined existing pathways and articulation models that enhance the participation of under-represented groups in higher education. Using the unqualified, diverse workforce in the economically significant discipline of the built environment, the project developed a best practice lifelong learning model that will improve the diversity of the student population in higher education. Dissemination of the exemplar processes and procedures of the model will enable adoption by all institutions in the sector, thus enhancing opportunities to satisfy diversity targets and goals.